An Examination of the Impact of Racial and Ethnic Identity, Impostor Feelings, and Minority Status Stress on the Mental Health of Black College Students. Issue 2 (April 2016) - McClain, Shannon; Beasley, Samuel T.; Jones, Bianca; Awosogba, Olufunke; Jackson, Stacey; Cokley, Kevin
Abstract : This study examined ethnic identity, racial centrality, minority status stress, and impostor feelings as predictors of mental health in a sample of 218 Black college students. Ethnic identity was found to be a significant positive predictor of mental health, whereas minority status stress and impostor feelings were significant negative predictors. Although ethnic identity was the strongest predictor of mental health, racial centrality represented a nonsignificant, negative predictor. Counseling implications for Black college students are discussed. Este estudio examinó la identidad étnica, la centralidad racial, el estrés por estatus de minoría y los sentimientos de impostor como indicadores de salud mental en una muestra de 218 estudiantes universitarios negros. Se halló que la identidad étnica es un indicador positivo significativo de salud mental, mientras que el estrés por estatus de minoría y los sentimientos de impostor fueron indicadores negativos significativos. Aunque la identidad étnica fue el indicador más fuerte de salud mental, la centralidad racial representó un indicador negativo no significativo. Se discuten las implicaciones para la consejería de estudiantes universitarios negros.